Sociology of Religion and the Aged: The Empirical Lacunae - Heenan, Edward F. (Journal for the scientific study of religion, 1972)
This study presents a comprehensive bibliography on the relation between religion and aging. One hundred and forty social science journals were surveyed, 80 from their inception and 60 over the last 25 years. The results reveal four major areas of research effort: (1) church participation, (2) religion and the personal adjustment of the aged, (3) the meaning of religion to older persons, and (4) religion and death. The results also show that sociologists of religion are responsible for only a small part of the literature on religion and aging. This finding is surprising in view of the significance attributed to death by most sociological theories of religion.